2022
DOI: 10.1111/oik.09229
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo climatic tolerances are decoupled from leaf functional traits across an Andean elevation gradient

Abstract: Widespread changes in temperature and precipitation patterns present plant species with new and combined stresses that affect their performance and distribution. Functional traits are indicators of plant resource use–acquisition strategies and thus they are commonly used to understand the geographic distributions of plant species and species' potential responses to climate change. To date, most studies have targeted a few easy‐to‐measure leaf traits even though other traits, such as climatic tolerances, could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 79 publications
3
8
2
Order By: Relevance
“…Contrary to recent hypotheses that physiological heat tolerance is coordinated with carbon economics (Knight & Ackerly, 2003;Sastry & Barua, 2017;Fadrique et al, 2022) and energy balance (Slot et al, 2021) traits, we observed that photosynthetic heat tolerance traits were orthogonal to carbon economics and energy balance traits. Although we observed remarkable variation in photosynthetic heat tolerance in our common garden (c. 40 to 51°C), this variation was not explained by phylogenetic structure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to recent hypotheses that physiological heat tolerance is coordinated with carbon economics (Knight & Ackerly, 2003;Sastry & Barua, 2017;Fadrique et al, 2022) and energy balance (Slot et al, 2021) traits, we observed that photosynthetic heat tolerance traits were orthogonal to carbon economics and energy balance traits. Although we observed remarkable variation in photosynthetic heat tolerance in our common garden (c. 40 to 51°C), this variation was not explained by phylogenetic structure.…”
Section: Discussioncontrasting
confidence: 99%
“…1b; Knight & Ackerly, 2003; Sastry et al ., 2018). However, support for this hypothesis is mixed, with some studies finding a positive association between heat tolerance and LMA (Knight & Ackerly, 2003; Sastry & Barua, 2017; Sastry et al ., 2018; Slot et al ., 2021; Li et al ., 2022) and others finding no such relationship (O'Sullivan et al ., 2017; Fadrique et al ., 2022; Münchinger et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SL has previously been used in laboratory and agricultural assays, but only a few very recent studies have used it to assess the drought tolerance of plants in the field. This is surprising, given that SL has many advantages that make it particularly well suited for studying the patterns of plant drought tolerances in biodiverse communities and in remote settings [ 59 , 60 ]. Specifically, the protocol is easy to follow and standardize, large numbers of treatments can be performed relatively quickly, the equipment needed for the experiments have a low-cost relative to other physiological measures of drought tolerance, and the measurements can be made in areas with little or no existing infrastructure (e.g., measuring SL does not require electricity or compressed gases and uses only distilled water and polyethylene glycol).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve hours after boiling, we took a second conductivity measurement (C 2 ). We calculated the relative solute leakage (%) as (C 1 − C 0 )/(C 2 − C 0 ) × 100 [ 59 , 60 ]. Higher SL values indicate greater cytorrhysis when exposed to desiccating conditions and thus a lower relative leaf drought tolerance.…”
Section: Methodsmentioning
confidence: 99%